Academic, Activist, or Advocate? Angry, Entangled, and Emerging: A Critical Reflection on Autism Knowledge Production - Botha, Monique (Frontiers in Psychology, 2021)
There has been a focus on autistic-led and participatory research in autism research, but minimal discussion about whether the field is hospitable to autistic involvement. While the focus on participatory and/or autistic-led research is abundantly welcome, a wider conversation should also happen about how autistic people are treated in the process of knowledge creation. As such, I present a critical reflection on my experiences of academia as an autistic autism researcher. I open by questioning whether I am an academic, an activist, or an advocate before discussing my journey through academia, and my exposure to dehumanizing, objectifying, and violent accounts of autism. I highlight how the construction of objectivity has resulted in a failure to question the validity of these dehumanizing accounts of autism, which are regarded as “scientifically-sound” by virtue of their perceived “objectivity.” Furthermore, I discuss how the idea of objectivity is used to side-line autistic expertise in disingenuous ways, especially when this knowledge challenges the status-quo. Despite claiming to be value-free, these dehumanizing accounts of autism embody social and cultural values, with a complete lack of transparency or acknowledgment. I then discuss how these dehumanizing accounts and theories—entangled in values—reverberate into autistic people's lives and come to be ways of constituting us. Following this, I discuss the rationality of the anger autistic people feel when encountering these accounts, and instead of urging people to distance themselves from these emotions, I discuss the value of “leaning-in” as a radical act of dissent in the face of research-based violence. I then make a call to action urging all those who write or speak about autism to engage reflexively with how their values shape their understanding and construction of autistic people. Lastly, I conclude by answering my opening question: I have emerged as an advocate, activist, and academic. For me, belonging to the autistic community, acknowledging our marginalization, and recognizing our suffering within society means that hope for a better and just future has always, and will always underpin my work.